(untitled) - Renata Kirita Doi SAMPAIO; Linda WANG; Rodrigo Varella de CARVALHO; Eugenio José GARCIA; Andréa Mello de ANDRADE; Celso Afonso KLEIN-JÚNIOR; Rosa Helena Miranda GRANDE; Sandra Kiss MOURA (University of São Paulo, 2013)
ObjectivesThis study aimed to compare the micro-tensile bond strength of methacrylate resin systems to a silorane-based restorative system on dentin after 24 hours and six months water storage.Material and MethodsThe restorative systems Adper Single Bond 2/Filtek Z350 (ASB), Clearfil SE Bond/Z350 (CF), Adper SE Plus/Z350 (ASEP) and P90 Adhesive System/Filtek P90 (P90) were applied on flat dentin surfaces of 20 third molars (n=5). The restored teeth were sectioned perpendicularly to the bonding interface to obtain sticks (0.8 mm2) to be tested after 24 hours (24 h) and 6 months (6 m) of water storage, in a universal testing machine at 0.5 mm/min. The data was analyzed via two-way Analysis of Variance/Bonferroni post hoc tests at 5% global significance.ResultsOverall outcomes did not indicate a statistical difference for the resin systems (p=0.26) nor time (p=0.62). No interaction between material × time was detected (p=0.28). Mean standard-deviation in MPa at 24 h and 6 m were: ASB 31.38 (4.53) and 30.06 (1.95), CF 34.26 (3.47) and 32.75 (4.18), ASEP 29.54 (4.14) and 33.47 (2.47), P90 30.27 (2.03) and 31.34 (2.19).ConclusionsThe silorane-based system showed a similar performance to methacrylate-based materials on dentin. All systems were stable in terms of bond strength up to 6 month of water storage.